RITUAL PELAKSANAAN TRADISI PACU JALUR DI DESA PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Susanti, Ena; Widodo, Teguh (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research was conducted in Pintu Gobang Kari Village, Kuantan Tengah Sub District, Kuantan Singingi Regency, Riau Province. The purpose of this study is to find out: 1) Know the ritual process of carrying out the Pacu Jalur tradition At Pintu Gobang Kari Village, Kuantan Tengah Sub District, Kuantan Singingi District. 2) Knowing how the people in Pintu Gobang Kari Village, Kuantan Tengah Sub District, Kuantan Singingi Regency, interpret the ritual process of carrying out the Pacu Jalur tradition. To achieve this goal, a descriptive qualitative research method was used by taking 4 people as the main informants and 1 person as a key informant (Key Informant). This study used a purposive sampling technique through observation, interviews and documentation. The results of research on how the ritual of carrying out the Pacu jalan tradition can be seen from the ritual process starting from the making of the track to the day of the race event which was so lively that was held at Tepian Narosa. Cutting a Big Tree is the first ritual performed by the jalan shaman, namely when he wants to cut down a large tree that he wants to make a boat for, this ritual has the meaning of asking permission from the caretaker of the big tree so that the wood can be taken without any hindrances or obstacles. Keywords: Rituals, Track, Magical